Breadth-first and depth-first search applied to educational games: case study in the Graph Defender game project - Pavani, Rafael Bogo; Campano Junior, Maurilio Martins; Aylon, Linnyer Beatrys Ruiz (Companion Proceedings of the Brazilian Symposium on Computer Games and Digital Entertainment (SBGames); 2023: Companion Proceedings of the 22nd Brazilian Symposium on Games and Digital EntertainmentDO - 10.5753/sbgames_estendido.2023.234060, 2023)
Games are a powerful entertainment tool for children, youth, and adults. When it comes to educational games, we associate learning with fun and playfulness. In Computer Science, a large portion of educational games addresses concepts such as Software Engineering and programming. Therefore, the aim of this work is to introduce the educational game ”Graph Defender,”focused on teaching graph search algorithms. The game was previously evaluated in a Software Engineering class during the Data Structures course, and the results indicate that the game is enjoyable while also fulfilling its educational role.